PENERAPAN AKAD MURABAHAH PADA PEMBIAYAAN MURABAHAH EMAS LOGAM MULIA DI PEGADAIAN SYARIAH MANDAILING NATAL - Jureid (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study aims to determine how the implementation of the Murabahah contracts in the financing of MULIA Metal Gold for Perpetual Investment in the Sharia Pawnshop of Mandailing Natal. The method used in this research is a qualitative descriptive method, which describes how the application of the financing contract is intended. The results of this study conclude that the MULIA financing contract at Panyabungan Syariah Pawnshop in carrying out its operational mechanism uses two contracts, namely the murabahah contract and the rahn contract. Where in the two contracts, the customer is required to pay an advance for commodity goods (precious metal gold) which will be used as collateral (marhun) and the determination of fines for late installment payments. This is usually done in business, due to the prudence of the Pawnshop in facing the risk of not being paid by the customer (default). Because considering the goods that are used as the object of the contract, are goods that have high economic value, namely gold, precious metals